Pengaruh Pembelajaran dengan Pendekatan Saintifik terhadap Motivasi dan Prestasi Belajar Mata Pelajaran Pendidikan Agama Islam pada Kelas VII SMP Negeri 1 Wringinanom Gresik - Vialinda Siswati (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
A glimpse of what is being taught Islam shows how much this religion intersect with science and education, for example, paragraphs 4 and 5 of Surah Al-Alaq, God Almighty, as a primary teacher, taught man what he did not know by means of a pen, « (5) يعلم لم ما الانسان علم) 4) ابلقلم علم الذی ,(when the Koran highlighted the importance of the pen as a tool for learning and spreading knowledge to swear to the pen, «يسطرون وما والقلم ن «ie